Modelling visual impressions for Chinese and Pakistani ethnic groups. (July 2020) - Mughal, Muhammad Farhan; Luo, Ming Ronnier; Pointer, Michael
Highlights: To identify visual impressions to accurately represent overall facial impressions. To clearly discern Chinese and Pakistani ethnic group's visual impression. To successful model facial impression from facial feature. To compare the performance with other models. New model performed better than other. Abstract: This work describes an investigation into the relationship between the visual impressions of a number of facial images each described by a set of parameters related to the position and size of discrete components: the eyes, the nose and the lips. Observations were made by members of two ethnic groups, Chinese and Pakistani, and the images comprised female faces from the same two groups. The observers used 16 impression scales to assess each image and a forced-choice scaling technique. From the factor analysis, the results showed that three visual impressions, attractive, feminine and mature, can well represent all the 16 scales. In the second experiment, the observers assessed visual impressions of more images using only these three impressions. Data are presented relating to the differences between the observations for the various facial locations, as well as between observers from different ethnic groups. Models have been developed that describe the data and their predictions outperformed traditional models, i.e.symmetry, golden ratio and neoclassical canons. The differences between the results of the two ethnic groups were found to be small; there were however, some significant differences in the responses to different facial features.